2016
DOI: 10.2527/jas.2016-0359
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide association analysis of growth traits in Charolais beef cattle1

Abstract: The objective of this study was to perform a genomewide association study (GWAS) for growth traits in Charolais beef cattle and to identify SNP markers and genes associated with these traits. Our study included 855 animals genotyped using 76,883 SNP from the GeneSeek Genomic Profiler Bovine HD panel. The examined phenotypic data included birth, weaning, and yearling weights as well as pre- and postweaning ADG. After quality control, 68,337 SNP and 823 animals were retained in the analysis. The association anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 45 publications
0
28
0
7
Order By: Relevance
“…in cattle. For HG and HH, many studies focus on only one growth stage, such as post-weaning height[19], yearling height[20], and stature in adulthood[13,21]. However, to date, no GWAS has been performed to evaluate the genetic architecture of HG and HH through the whole growing period in cattle.…”
Section: Introductionmentioning
confidence: 99%
“…in cattle. For HG and HH, many studies focus on only one growth stage, such as post-weaning height[19], yearling height[20], and stature in adulthood[13,21]. However, to date, no GWAS has been performed to evaluate the genetic architecture of HG and HH through the whole growing period in cattle.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported QTLs and genes associated with growth traits in cattle (e.g., body weight and average daily gain) using the GWAS strategy [40,41]. However, few QTLs have consistently been identified as being associated with growth traits among breeds of cattle, including for Brangus heifers [42], Japanese Black (Wagyu) cattle [43], Charolais beef cattle [8], Siberia cattle [1], Nellore cattle [3], and the Chinese Simmental beef cattle examined in this study. These findings imply that further in-depth research is required to determine whether breed-specific QTLs exist.…”
Section: Potential Genomic Regions and Candidate Genes Reveal The Commentioning
confidence: 87%
“…Buzanskas et al [7] performed a GWAS in 404 Canchim beef cattle using BovineHD BeadChip and found four SNPs associated with birth weight. Jahuey-Martinez et al [8] found 18 SNPs located in 13 Bos taurus chromosomes (BTA) and highlighted five genes (TRAF6, CDH11, KLF7, MIR181A-1 and PRCP) that were associated with growth traits in a population of 855 Charolais beef cattle genotyped for 76,883 SNPs. Although some progress has been made, the genetic architecture of these economically important traits remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For beef cattle, birth weight is an important trait that represents the first phenotypic variable of a new individual in a population and is also considered an indicator of calving ease (Canellas et al, 2012). Furthermore, for beef cattle producers, calves with greater weights at weaning have the advantage of being more morphologically developed and better equipped to successfully cope with the environment (Jahuey-Martínez et al, 2016).…”
Section: Introductionmentioning
confidence: 99%